Islamic Human Capital Management and Compensation as Drivers of Employee Productivity: Insights from a Small Service Enterprise in Indonesia - Ahmad Syarif; Bisma Maulana (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
The disparity in employee productivity among organizations within the same industry has necessitated advancements in human resource management. Consequently, Islamic Human Capital management emerges as a practical approach to enhance staff productivity. This research, conducted at Istana Laundry Samarinda, aims to provide insights into how Islamic Human Capital management and remuneration influence staff productivity, offering valuable guidance for HR strategies. The study employed quantitative methodologies with a sample of 65 employees. A Likert-scale questionnaire was used as the instrument. Multiple linear regression analysis was utilized as one of the analytical strategies. The findings suggest that Islamic Human Capital management enhances employee productivity, whereas remuneration does not. Based on these results, it is recommended that Istana Laundry improve its Islamic Human Capital management and evaluate its compensation system to boost employee productivity.